Peptide valence-induced breaks in plasmonic coupling - Chang, Yu-Ci (2023)
Electrostatic interactions are a key driving force that mediates colloidal assembly. The Schulze-Hardy rule states that nanoparticles have a higher tendency to coagulate in the presence of counterions with high charge valence. However, it is unclear how the Schulze-Hardy rule works when the simple electrolytes are replaced with more sophisticated charge carriers. Here, we designed cationic peptides of varying valencies and demonstrate that their charge screening behaviors on anionic gold nanoparticles (AuNPs) follow the six-power relationship in the Schulze-Hardy rule. This finding further inspires a simple yet effective strategy for measuring SARS-CoV-2 main protease (Mpro) via naked eyes. This work provides a unique avenue for fundamental NP disassembly based on the Schulze-Hardy rule and can help design versatile substrates for colorimetric sensing of other proteases.